Attenuation of Oxidative Damage via Upregulating Nrf2/HO-1 Signaling Pathway by Protease SH21 with Exerting Anti-Inflammatory and Anticancer Properties In Vitro - Hasan Tarek; Seung Sik Cho; Md. Selim Hossain; Jin Cheol Yoo (Cells, 2023)
Oxidative damage and inflammation are among the very significant aspects interrelated with cancer and other degenerative diseases. In this study, we investigated the biological activities of a 25 kDa protease (SH21) that was purified from Bacillus siamensis. SH21 exhibited very powerful antioxidant and reactive oxygen species (ROS) generation inhibition activity in a dose-dependent approach. The mRNA and protein levels of antioxidant enzymes such as superoxide dismutase 1 (SOD1), catalase (CAT), and glutathione peroxidase 1 (GPx-1) were enhanced in the SH21-treated sample. SH21 also increased the transcriptional and translational activities of NF-E2-related factor 2 (Nrf2) with the subsequent development of detoxifying enzyme heme oxygenase-1 (HO-1). In addition, SH21 showed potential anti-inflammatory activity via inhibition of nitric oxide (NO) and proinflammatory cytokines, such as TNF-α, IL-6, and IL-1β, production in lipopolysaccharide (LPS)-stimulated RAW 264.7 cells. At concentrations of 60, 80, and 100 μg/mL, SH21 potentially suppressed nitric oxide synthase (iNOS) and cytokine gene expressions. Furthermore, SH21 significantly released lactate dehydrogenase (LDH) enzyme in cancer cell supernatant in a concentration-dependent manner and showed strong activity against three tested cancer cell lines, including HL-60, A549, and Hela. Our results suggest that SH21 has effective antioxidant, anti-inflammatory, and anticancer effects and could be an excellent therapeutic agent against inflammation-related diseases.